The border as liminal space - Marie-Christine Fourny (Revue de Géographie Alpine)
This article examines the concept of liminality as it relates to the terms ‘border’ and ‘limit’. It shows that early anthropological approaches refer to liminal space as a means of managing the dynamic relationship with the norm in a social structure. In more recent analyses, liminality is used to demonstrate the way in which situations of otherness develop, in a complex interplay of power, place, and social and spatial norms. Analysis of the project to develop a macro-regional strategy for the Alps provides an illustration of this. Thus, the MRS project aims to unite an “Alps” space around common objectives. It raises the question of the alpine border, whether in the context of national borders to be crossed, the limit of the mountain area to be moved, or the area of the Alpine Arc to be defined. Representations that are found of the alpine limit lead us to conclude that a liminal alpine space can be constructed in both a cognitive and functional sense.